Very large phase shift of microwave signals in a 6 nm HfxZr1−xO2 ferroelectric at ±3 V. (31st August 2017) - Dragoman, Mircea; Modreanu, Mircea; Povey, Ian M; Iordanescu, Sergiu; Aldrigo, Martino; Romanitan, Cosmin; Vasilache, Dan; Dinescu, Adrian; Dragoman, Daniela
Abstract: In this letter, we report for the first time very large phase shifts of microwaves in the 1–10 GHz range, in a 1 mm long gold coplanar interdigitated structure deposited over a 6 nm Hf x Zr1− x O2 ferroelectric grown directly on a high resistivity silicon substrate. The phase shift is larger than 60° at 1 GHz and 13° at 10 GHz at maximum applied DC voltages of ±3 V, which can be supplied by a simple commercial battery. In this way, we demonstrate experimentally that the new ferroelectrics based on HfO2 could play an important role in the future development of wireless communication systems for very low power applications.